2001
DOI: 10.1007/bf03016825
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine as adjuvant for mepivacaine, ropivacaine and bupivacaine in axillary, perivascular brachial plexus block

Abstract: Purpose: To evaluate the effects of clonidine on three local anesthetics (mepivacaine 1%, ropivacaine 0.75% and bupivacaine 0.5%) with comparable potency and almost the same concentration-response relationship.Methods: One hundred and twenty trauma-patients were randomly allocated into six groups. In the control-groups (Mo/Ro/Bo) brachial plexus was performed using 40 mL of local anesthetic plus 1 mL of NaCL 0.9%. In the clonidine-groups (Mc/Rc/Bc) brachial plexus was performed using each 40 mL of drug plus 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
36
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 10 publications
8
36
2
2
Order By: Relevance
“…Which was also found with studies conducted by Francois J Singelyn et al 13 and Jean J Eledjam et al 15 using Lidocaine and mepivacaine respectively. Similar observation was found in the studies conducted by Duma et al 16 and Erlacher W et al Where the onset time was prolonged as long acting local anesthetics were used unlike intermediate acting local anesthetics like Lidocaine which was used in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Which was also found with studies conducted by Francois J Singelyn et al 13 and Jean J Eledjam et al 15 using Lidocaine and mepivacaine respectively. Similar observation was found in the studies conducted by Duma et al 16 and Erlacher W et al Where the onset time was prolonged as long acting local anesthetics were used unlike intermediate acting local anesthetics like Lidocaine which was used in our study.…”
Section: Discussionsupporting
confidence: 81%
“…16,17 Casati 18 evaluated the effects of clonidine 1 mcg/kg added to ropivacaine and found longer onset of time to establish block in clonidine group. Erlacher et al 19 compared the effect of adding clonidine to different LAs like mepivacaine, bupivacaine and ropivacaine and found that clonidine has a different impact on each of the LAs in terms of onset and block prolonging action.…”
Section: Discussionmentioning
confidence: 99%
“…It supports the analgesic action at peripheral sites. 4 Dexmedetomidine, a selective α2-adrenoceptor agonist, has been used as an adjuvant during regional and local anesthesia. 5,6 Animal and human studies have shown safety and efficacy of adding dexmedetomidine to local anaesthetics in various regional anaesthetic procedures, such as subarachnoid, epidural, and caudal injections, yet other investigations have reported reduced or negative analgesic effects when using dexmedetomidine.…”
Section: Introductionmentioning
confidence: 99%